Deepfakes’ Challenge to International Politics: Sowing Political Discord - Kafayat, Sobia (Annals of Human and Social Sciences, 2025)
This research aims to investigate the effect that deepfakes (as an evolving phenomenon) can have on International Politics (as it currently exists). Deepfake is a form of artificial intelligence that produces realistic fake videos, pictures, images, or text. The term deepfake technology combines “deep learning” and “fake.” Deepfakes can change the sources of original materials, such as voice, face, or images, by replacing one person with another. Deepfakes are becoming increasingly relevant in today’s digitized world due to their ability to create highly realistic yet fabricated content that blurs the distinction between reality and fiction. Based on a characterization of contemporary global politics, this study draws evidence from case studies. The research is qualitative and uses the secondary method of research. Though divergence among actors might naturally exist, discord sown by deepfakes reinforces the divisiveness, thus impacting international politics adversely. Remedial measures do not fall within the scope of this study.